Handbook of project management procedures - Hamilton, Albert (Thomas Telford, 2004)
This definitive guide presents a comprehensive set of step-by-step best practice procedures for managing any type of project from concept to completion. It is not academic, it is not of a general nature, but provides working standards and practices in the recognised project management areas.